Ethnographic research on children's literacy practices: children's literacy experiences and possibilities for representation. Issue 1 (2nd January 2020) - Schmidt, Catarina
ABSTRACT: This paper draws on a longitudinal ethnography of nine children's use of texts in and out of school in a multilingual setting in Sweden. The aim of this contribution is to reflect on the ways in which four out of these nine children are able to represent their literacies in school and in that way also represent their experiences and identities. The analysis highlights the importance of ethnographic approaches through which literacies can be studied from children's perspectives rather than using predefined and technical definitions. Drawing on the results, I argue that studies of children's literacy practices have to be related to children's positions and to power structures within society and its institutions. The crucial goal in this is to avoid deficit discourses, to challenge narrow classroom discourses and to sustain democracy in diverse societies.